Development of Machine Tool Disassembly and Assembly Training and Digital Twin Model Building System based on Virtual Simulation - Zhao, Guan; Wang, Yanfei (International Journal of Mechanical and Electrical Engineering, 2024)
In response to the issues of poor safety and insufficient training equipment in traditional machine tool assembly and disassembly training, this paper proposes a machine tool assembly and disassembly training system based on virtual simulation. The system utilizes Unity 3D to construct an interactive virtual training environment, achieving highly simulated simulations and teaching of the machine tool assembly and disassembly process. Additionally, the system is capable of establishing communication with actual machine tools, achieving bidirectional mapping between digital and physical spaces, allowing learners to observe the dynamic responses of machine tool models through the virtual environment. This virtual-real interaction mechanism enriches the application scenarios of the system, introducing digital twin technology into the virtual simulation of machine tool assembly and disassembly training. This paper also provides a detailed introduction to the design and implementation of core technologies such as the system's overall architecture, scene modeling, and virtual-real interaction, offering significant support for intelligent teaching in machine tool assembly and disassembly.